MAKASSAR SPEAK ACTS IN BUYING AND BUYING INTERACTIONS IN THE PATTALLASSANG MARKET TAKALAR DISTRICT - Rahmatia, Rahmatia; Agussalim AJ, Andi; Nojeng, Asis (Media Inovasi Pendidikan dan Publikasi, 2025)
The aim of this research is to describe the forms of conversation and illocutionary speech acts of Makassar people in the interaction between sellers and buyers at the Pattallassang Market district. This type of research is qualitative descriptive research. The methods used in collecting data for this research were observation, recording techniques and document analysis. Data analysis in this research begins with describing the data in the form of recorded conversation data in the field, the next process is identifying the data, and data reduction is carried out. The validity of the data is obtained from the triangulation process using theoretical triangulation techniques. The results of this research show that the speech acts found in the interaction between sellers and buyers, assertive speech acts, are (1) mentioning, (2) speculating, (3) reporting, (4) admitting, (5) proposing and (6) complaining. Acting directive speech acts, namely, offering.